Hospital readmission after a pancreaticoduodenectomy: an emerging quality metric?. Issue 2 (24th September 2012) - Kastenberg, Zachary J.; Morton, John M.; Visser, Brendan C.; Norton, Jeffrey A.; Poultsides, George A.
Abstract Background Hospital readmission has attracted attention from policymakers as a measure of quality and a target for cost reduction. The aim of the study was to evaluate the frequency and patterns of rehospitalization after a pancreaticoduodenectomy (PD). Methods The records of all patients undergoing a PD at an academic medical centre for malignant or benign diagnoses between January 2006 and September 2011 were retrospectively reviewed. The incidence, aetiology and predictors of subsequent readmission(s) were analysed. Results Of 257 consecutive patients who underwent a PD, 50 (19.7%) were readmitted within 30 days from discharge. Both the presence of any post‐operative complication (P = 0.049) and discharge to a nursing/rehabilitation facility or to home with health care services (P = 0.018) were associated with readmission. The most common reasons for readmission were diet intolerance (36.0%), pancreatic fistula/abscess (26.0%) and superficial wound infection (8.0%). Nine (18.0%) readmissions had lengths of stay of 2 days or less and in four of those (8.0%) diagnostic evaluation was eventually negative. Conclusion Approximately one‐fifth of patients require hospital readmission within 30 days of discharge after a PD. A small fraction of these readmissions are short (2 days or less) and may be preventable or manageable in the outpatient setting.